L’ingérence inattendue du Ministère de l’Enseignement Supérieur et de la Recherche Scientifique dans le recouvrement et la gestion des ressources propres des Universités publiques de Côte d’Ivoire - Fêtê Ernest, Dr KOFFI (International Journal of Scientific Research and Management (IJSRM), 2022)
Ivorian public universities are classified in the category of National Public Establishments (EPN). As such, they must generate their own resources and seek additional resources to supplement the subsidies that the State grants them. In recent years, it has been observed not only the confiscation by the State of 70% of tuition fees (commitment not respected), but the unexpected interference of their technical supervision in the recovery and management of their own resources.This situation refers to the thorny and complex issue of the autonomy of Ivorian public universities in general and particularly their financial management. In the current context, it is necessary to discuss it between the State and the academic world to take into account the concerns of each stakeholder, in the interest of Ivorian higher education